What research on early childhood education/care outcomes can, and can't tell policymakers - Wylie, Cathy, 1951- (New Zealand Council for Educational Research, 1994)
Introduction. Research on early childhood education/care-some necessary background. Outcomes of early childhood education/care. Funding and regulation factors bearing on the provision of early educare...